1985
DOI: 10.7863/jum.1985.4.8.393
|View full text |Cite
|
Sign up to set email alerts
|

The value of ultrasonography as a screening procedure in a first-documented urinary tract infection in children.

Abstract: To evaluate the role of ultrasonography in the investigation of childhood urinary tract infections (UTI), 240 patients aged 2 days to 15 years with a first-documented UTI were examined first by sonography, then by intravenous urography (IVU), and when indicated by voiding cysto-urethrogram (VCU). According to the results of these examinations, the patients were divided into three groups. In Group 1 (71 patients), abnormal sonographic findings were confirmed by the radiographic studies. Patients in Group 2 (51 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…In the present study, the grade of dilatation on ultrasonography was not defined, but it should be noted that dilatation was directly related to the presence and severity of reflux. Renal ultrasonography is usually recommended as a first-line investigation in children with UTI, in order to exclude urinary obstruction (18). This study confirms previous observations that dilatation of the renal pelvis without urinary obstruction frequently indicates the presence of dilated reflux (19).…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, the grade of dilatation on ultrasonography was not defined, but it should be noted that dilatation was directly related to the presence and severity of reflux. Renal ultrasonography is usually recommended as a first-line investigation in children with UTI, in order to exclude urinary obstruction (18). This study confirms previous observations that dilatation of the renal pelvis without urinary obstruction frequently indicates the presence of dilated reflux (19).…”
Section: Discussionsupporting
confidence: 89%
“…Eight studies reporting 17 data sets examined the performance of a variety of tests, and combinations of tests, to detect groups of renal and urinary tract pathologies 122,151,159,161,170,194,203,216 (Table 29). The studies used a wide variety of tests and test combinations as reference standards.…”
Section: Imaging Studies With Multiple Aimsmentioning
confidence: 99%
“…It is prudent to begin the US examination with views of the bladder in the younger child since micturition may occur during the examination, preventing evaluation of the lower ureters later. Numerous studies have shown the high sensitivity and specificity of US as a screening procedure for children with UTI compared with the IVU (Jaquier et al, 1983;Sherwood & Whitaker, 1984;Kangarloo et al, 1985;Whyte et al, 1988). If scarring is detected on US then there is no reason to doubt its existence but a normal US does not exclude a renal scar.…”
Section: Imaging Controversymentioning
confidence: 95%
“…Currently all children with UTI shoud have a plain abdominal radiograph as well as an US of the kidneys and bladder to exclude urinary calculi, nephrocalcinosis and obstructive uropathy, as well as to measure the renal size (Jaquier et al, 1983;Sherwood & Whitaker, 1984;Kangarloo et al, 1985;Whyte et al, 1980). If the US is normal then no further investigations should be undertaken in children older than 5 years.…”
Section: Imaging Controversymentioning
confidence: 96%